1997
DOI: 10.1108/09596119710185846
|View full text |Cite
|
Sign up to set email alerts
|

Using the contribution margin aspect of menu engineering to enhance financial results

Abstract: Managing food service operations to achieve a specific food cost percentage has long been a fundamental principle of the restaurant business. Management bonuses and other rewards are often based on achieving these predetermined goals. Available tools such as menu engineering and contribution margin, although sound in theory, are not frequently used. Demonstrates the use of menu engineering and contribution margin concepts in terms of customers served. Concludes that the goal of any restaurant should be to appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 1 publication
0
15
1
Order By: Relevance
“…This is particularly relevant given the twin conclusions of past research that, firstly, the industry lags in the monitoring and control of business results (LeBruto et al, 1997;Mann et al, 1999a), and secondly, powerful retailers treat suppliers' cost management systems as an important criterion when developing supply chain relationships (Fearne and Hughes, 1999). Our findings are based on the analysis of 122 questionnaires completed by management accountants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly relevant given the twin conclusions of past research that, firstly, the industry lags in the monitoring and control of business results (LeBruto et al, 1997;Mann et al, 1999a), and secondly, powerful retailers treat suppliers' cost management systems as an important criterion when developing supply chain relationships (Fearne and Hughes, 1999). Our findings are based on the analysis of 122 questionnaires completed by management accountants.…”
Section: Discussionmentioning
confidence: 99%
“…Drury et al (1993) found that only 3% of respondents always or often used regression techniques, and 6% often or always used probability analysis. However, they argued that the advancement of such techniques in textbooks would lead to their wide adoption; for instance regression analysis was recommended by LeBruto et al (1997) for separating fixed and variable costs in the food industry. The results of our survey do not support this expectation.…”
Section: Discussion and Further Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Kasavana and Smith (1982) and LeBruto et al (1995LeBruto et al ( , 1997 underline that the computation of a dish's profitability is by measuring the number of dollars generated per unit sale but not the food cost percentage, as the latter variable cannot be deposited in banks. In menu engineering, an entr!…”
Section: Application Of Menu Engineeringmentioning
confidence: 98%
“…This is because the latter variables are assumed, ''yequally related to all menu itemsy'' and thus, can be ignored (Kasavana and Smith, 1990, p. 126). LeBruto et al (1995LeBruto et al ( , 1997 suggest that linear regression analysis can clearly distinguish the fixed costs from variable costs and argue that all variable costs should be included in order to compute the ''true'' net profit for individual dishes.…”
Section: Imperfections Of the Early Approachesmentioning
confidence: 99%